An Eu/Tb-codoped inorganic apatite Ca5(PO4)3F luminescent thermometer. Issue 5 (June 2015) - Fu, Linlin; Fu, Zuoling; Yu, Yingning; Wu, Zhijian; Jeong, Jung Hyun
Abstract: A new Eu/Tb-codoped inorganic apatite Ca5 (PO4 )3 F luminescent thermometer has been targeted. Under ultraviolet irradiation, the Ca5 (PO4 )3 F:Tb 3+ /Eu 3+ samples exhibit a blue-light emission of the host matrix which might originate from the CO 2 − radical-related defect produced by Cit 3− groups, as well as the typical green emission band of the Tb 3+ ions, and a red-light emission of Eu 3+ . These lanthanide-based thermometers (Ca5 (PO4 )3 F:Tb 3+ /Eu 3+ ) exhibit different sensitivities ranging from different temperatures based on two emissions of Tb 3+ at 548 nm and Eu 3+ at 621 nm. The temperature-dependent luminescent intensity ratios I Tb / I Eu can be optimized by the controlled relatively doping of different amounts of Tb 3+ and Eu 3+ ions.